DDDR-25. CO-INHIBITION OF KINASE SIGNALING PATHWAYS AND EPIGENETIC REGULATORS OVERCOMES COMPENSATORY EFFECTS IN PEDIATRIC HIGH-GRADE GLIOMAS. (14th November 2022) - Adams, Jack; Stitzlein, Lea; Singh, Melissa; Su, Xiaoping; Lu, Yue; Bailey, Cavan; Monje, Michelle; Whitehead, Christopher; Sebolt-Leopold, Judith; Chandra, Joya
Abstract: Pediatric high-grade gliomas (pHGG) confer poor survival outcomes with minimal treatment options due to a high rate of therapeutic resistance and few surgical options. One subgroup of pHGG is diffuse intrinsic pontine glioma (DIPG). Patient-derived cell lines, such as SU-DIPG-XIII, SU-DIPG-VI, and SU-DIPG-IV, recapitulate epigenetic mutations seen in patients. In these lines, lysine-specific demethylase 1 (LSD1) is overexpressed and knockdown/inhibition slows growth, therefore, optimizing LSD1 inhibitor treatment regimens is promising. In other models, MEK kinase activation acts as a mechanism of resistance to LSD1 inhibitors. This is relevant to DIPG due to the frequency of dysregulated and mutated upstream kinase pathways. Thus, we sought to identify the connection between LSD1 and kinase signaling as a therapeutic co-inhibition strategy in DIPG. Pharmacologically relevant catalytic LSD1 inhibitors were assessed using the alamarBlue viability assay and demonstrated wide ranges of IC₅₀ values with ORY-1001(19 μM to > 150 μM), ORY-2001( > 50 μM), GSK-LSD1(134 μM to > 500 μM), and IMG-7289(1.6 μM-179 μM) in the SU-DIPG lines. Resistance mechanisms from kinase modulation were investigated via Western Blot to determine if kinase inhibition could sensitize these cells to LSD1 inhibition. We discovered that LSD1 inhibition caused an unexpected increase in pAKT and pERK, suggesting enhanced activity of protumorigenic kinases. To overcome kinase activation from LSD1 inhibition, MEK or PI3K inhibitors, including selumetinib, trametinib, and BKM120, were tested. A novel dual kinase inhibitor directed against EGFR and PI3K, MTX-241F, was also assessed. Several combinations caused a significant increase in efficacy measured by cell viability. We further observed that the addition of kinase inhibitors with LSD1 inhibition decreased phosphorylated kinases. Overall, the combination enhanced in vitro efficacy in contrast to single-agent inhibition supporting an interplay between LSD1 and kinase signaling in pHGG. Future studies will assess this combination utilizing orthotopic xenograft models of DIPG